Influence of different test strategies on the power cycling test results of 6.5 kV SiC MOSFETs. (November 2021) - Gerlach, M.; Boldyrjew-Mast, R.; Bruchhold, F.; Lutz, J.; Basler, T.; Schwarzmann, H.
Abstract: When silicon carbide power devices are subjected to power cycling tests, specific aspects must be considered for the evaluation of test results in order to investigate aging mechanisms of the packaging technology. A threshold voltage drift as well as bipolar degradation can influence the results depending on the test procedure, while a higher probability of bipolar degradation is given, especially for high-voltage devices. In this paper, four 6.5 kV modules with standard packaging technology have been investigated with two different test procedures in power cycling tests. Highlights: Influence of different test strategies on power cycling test results of 6.5 kV SiC MOSFETs including MOSFET- and diode-mode Measurements of the threshold voltage with preconditioning to capture the hysteresis and bias temperature instability Measurement of junction temperature with VSD (T)-method and the impact of the threshold voltage shift on calibration curves Solder degradation between die and substrate as dominating failure mechanism in the PCT under given test conditions